Hikmah dan Etika Ibadah Haji dalam QS. Al-Baqarah Ayat 197 - Hilya Mahfuza; Edi Hermanto; Syifa Farizkha Indriani; Warda Mardiana Tambunan (Indo Publishing, 2026)
This study aims to examine the wisdom and ethical values of the Hajj pilgrimage as contained in QS. Al-Baqarah verse 197 and their relevance to the life of Muslims. The research employs a qualitative approach using a library research method. Data are obtained from the Qur’an, particularly QS. Al-Baqarah verse 197, the hadiths of the Prophet Muhammad (peace be upon him), as well as classical and contemporary Qur’anic commentaries, books on Hajj jurisprudence, and relevant Islamic literature. Data analysis is conducted through a descriptive-analytical method to explore the meanings, ethical principles, and spiritual values of Hajj, such as the prohibition of rafath, fusuq, and jidal, and the emphasis on piety (taqwa) as the best provision. The findings indicate that Hajj is not merely an individual ritual worship but also contains strong moral, spiritual, and social dimensions that encourage Muslims to develop both personal piety and social responsibility in their daily lives.